Tillage Intensity in a Long-Term Wheat-Sorghum-Fallow Rotation - A. Schlegel; A. Burnett (Kansas Agricultural Experiment Station Research Reports, 2019)
This study was initiated in 1991 at the Kansas State University Southwest Research-Extension Center near Tribune, KS. The purpose of the study was to identify the effects of tillage intensity on precipitation capture, soil water storage, and grain yield in a wheat-sorghum-fallow rotation. Grain yields of wheat and grain sorghum increased with decreased tillage intensity in a wheat-sorghum-fallow (WSF) rotation. In 2018, available soil water at sorghum planting was greater for no-tillage (NT) than reduced tillage (RT) which was greater than conventional tillage (CT). For wheat there was a similar pattern as sorghum, with available soil water at wheat planting being in the order of NT>RT>CT. Averaged across the 18-yr study, available soil water at wheat planting was similar for NT and RT and approximately 1 inch greater than CT. Average available soil water at sorghum planting was greater in the order RT≥NT>CT. Averaged across the past 18 years, NT wheat yields were 5 bu/a greater than RT and 8 bu/a greater than CT. Grain sorghum yields in 2018 were twice as great in long-term NT compared to short-term NT with the lowest yields with CT. Averaged across the past 18 years, sorghum yields with long-term NT have been 58% greater than with short-term NT (76 vs. 48 bu/a).
Keywords: no-till; conventional tillage; soil water; grain yield